2009
DOI: 10.1159/000234907
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posterior Capsular Opacification between a Combined Procedure and a Sequential Procedure of Pars Plana Vitrectomy and Cataract Surgery

Abstract: Purpose: To compare posterior capsular opacification (PCO) between a combined procedure and a sequential procedure of pars plana vitrectomy (PPV) and cataract surgery (CS). Methods: The medical records of 89 eyes of 85 patients who underwent PPV and CS were retrospectively reviewed. There were 56 eyes of 52 patients with a combined PPV and CS (the combined surgery group), and 33 eyes of 33 patients with CS in a previously vitrectomized eye (the sequential surgery group). The control group was comprised of 130 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
1
11
1
1
Order By: Relevance
“…2,11 Posterior capsule opacification is also reported to occur more frequently after phacovitrectomy (12.5%) than after phacoemulsification and IOL implantation alone (4.6%). 12 Our study also supports existing data showing that posterior capsulotomy is a practical method for preventing postoperative PCO in patients with vitreoretinal disease who require a phacovitrectomy. 10 However, our study also found that posterior capsulotomy did not prevent PCO in every case.…”
Section: Discussionsupporting
confidence: 89%
“…2,11 Posterior capsule opacification is also reported to occur more frequently after phacovitrectomy (12.5%) than after phacoemulsification and IOL implantation alone (4.6%). 12 Our study also supports existing data showing that posterior capsulotomy is a practical method for preventing postoperative PCO in patients with vitreoretinal disease who require a phacovitrectomy. 10 However, our study also found that posterior capsulotomy did not prevent PCO in every case.…”
Section: Discussionsupporting
confidence: 89%
“…Rahman et al assumed that this discrepancy was due to the effect of posterior vitreous pressure on PCO. Furthermore, sequential cataract surgery after vitrectomy has been shown to lead to a higher incidence of PCO than combined surgery [18]. In our study, Nd:YAG capsulotomy free survival times showed no difference in both surgical option groups by both statistical comparison and survival plot.…”
Section: Resultsmentioning
confidence: 43%
“…As age and diabetes may be related to the rate of PCO after phacovitrectomy or cataract surgery only [17, 29], these intergroup differences may have introduced bias into our study. However, the use of age matching reduced the potential influence of this bias and age and diabetes were not identified as risk factors, which has also been noted in a previous study [18]. Furthermore, we retrospectively evaluated the surgical outcomes during longer period, so evolution of surgical techniques and surgical instruments, especially intraocular lenses, could be potential bias of this study.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been a few reports regarding the development of PCO following phacovitrectomy. 3,4,6,14 However, those studies included several kinds of disease and used various procedures, including gas tamponade, indicating that those results could be affected by selection bias. Thus, in this report, the same three procedures were performed for each ERM case; cataract surgery, core vitrectomy, and ERM peeling.…”
Section: Resultsmentioning
confidence: 99%